New Opportunities in the Structure-based Design of Anti-Protozoan Agents - A. Gordon, James; W.G. Fishwick, Colin; J. McPhillie, Martin (Current Topics in Medicinal Chemistry, 2017)
Since the recent renaissance of phenotypic screening in the field of protozoan drug discovery, is there still an opportunity for the structure-based design of new anti-protozoan agents? Target-based approaches should be used in parallel to phenotypic screening to strengthen the pipeline of anti-protozoan agents. We give an overview of the protozoan drug discovery landscape highlighting four protein targets of interest: cytochrome bc1, dihydroorotate dehydrogenase, dihydrofolate reductase and calcium-dependent protein kinase 1. We discuss recent structurebased design efforts to inhibit these targets, reviewing their crystal structures and their ability to accommodate potent and selective compounds. Finally, we discuss future opportunities to apply structure-based methods to promising molecular targets within protozoan parasites discovered using chemical genomics.
Keywords: DHODH